What drives endogenous growth in the United States? - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2010)
This paper estimates whether learning-by-doing effects or cleansing effects of recessions drive the endogenous component of productivity in the United States. Using Bayesian estimation techniques we find that external and internal learning-by-doing effects dominate. We find no evidence for cleansing effects of recessions. Furthermore, the exogenous component of productivity growth is close to the two percent pace.
Keywords: C11; E32; O40; 330; Business Cycles; Cleansing Effects of Recessions; Endogenous Growth; Learning-by-Doing; Produktivität; Neue Wachstumstheorie; Lernprozess; Konjunktur; Schätzung; USA